Unlocking Academic success through translanguaging: Summary writing at a South African University - Chihobo, Akulina; Makalela, Leketi (Critical Studies in Teaching and Learning, 2025)
Summary writing is a core academic activity essential for success in higher education. Proficiency in this skill is crucial for students to perform various academic tasks. However, summary writing poses significant challenges for multilingual students in South Africa, particularly in contexts where monolingual practices prevail. This qualitative study investigates the impact of translanguaging on the summary writing skills of multilingual students at a South African university. Eight participants, who wrote summaries of an English text in English and their home languages, were interviewed in semi-structured interviews. The findings reveal that translanguaging enhances comprehension and engagement with texts, as it allows students to use multiple languages freely. Consequently, this paper recommends implementing language policies that treat all languages equally and encourage the use of students’ home languages as learning resources. Future research should focus on incorporating texts in multiple languages for reading and summary writing in literacy education.